Effectiveness of Video and Leaflet about BSE (Breast Self Examination) on Changes in Teenage Behavior - Ajeng, Atnesia; Zuhrotunida, Zuhrotunida; Indriani, Rini Yunita (International Conference on Sustainable Health Promotion, 2018)
According to GLOBOCAN (IARC) data in 2012 it was found that breast cancer is a cancer with the highest percentage of new cases (after being controlled by age), which is 43.3%, and the percentage of deaths due to breast cancer is 12.9 %. Breast Self Examination (BSE) is the easiest detection of breast cancer compared to the others, namely breast examination by health personnel and mammography examination. Generally, breast cancer is detected first by the sufferer himself. This information exposure is very important because it increases the knowledge of young women about breast cancer and the dangers and ways to make early detection of breast cancer. The purpose of this study was to find out the effectiveness of Videos and Leaflets about breast self-examination (breast self-examination) on changes in adolescent behavior. The study population was high school teenagers throughout the city of Tangerang. Sampling technique with Random Sampling (Probability Sampling. The statistical test used is man-whitney and independent samples t-test obtained Video results are more effective than leaflet even though there is no significant difference in effect on health education with video compared to leaflets in changes in adolescent behavior about awareness.